Automatic Visual Inspection Reconfigurable Model of Piston Assembly Based on Extentics - Jili Lu; Mingxing Lin; Fenghua Ding; Qingdong Wang (Institute of Advanced Engineering and Science, 2014)
As a visual inspection system can’t meet all the testing demands of various types of piston assembly, a visual inspection reconfigurable model for piston assembly was designed. A five-layer gray box model was established based on analyzing the process of visual inspection, and expressed by extension element; On this basis, a foundation scheme library was made using extension transform and generation strategy; The optical scheme was evaluated and chose by Analytic Hierarchy Process (AHP).This model can realize reconfigurable visual inspection automatically, improve the adaptability of visual inspection, solve the contradictions between custom requirements and existing condition, time and production cost .